Between Adaptation and Resistance: A Study on Resilience Competencies, Stress, and Well-Being in German VET Teachers - Kärner, Tobias; Bottling, Matthias; Friederichs, Edgar; Sembill, Detlef (Frontiers in Psychology, 2021)
We demonstrate the relationships between occupational demands in German vocational education and training (VET) teacher training, stress symptoms, and different behavioral resilience competencies. Taking into account interindividual differences in resilience competencies, we use a typological approach to identify different types of (trainee) teachers classified by their degrees and configurations of resilience competencies. Our empirical analysis is based on questionnaire data from 131 German vocational trainees and qualified teachers. The results reveal, among other things, that all three resilience competencies—resistance, flexibility, and dynamism—are significantly negatively correlated with the demands of working conditions and workload. Via a latent class analysis, we were able to identify three groups of (trainee) teachers who differed in their resilience competencies to adapt appropriately to different situations and their requirements (“behavioral flexibility”), to recover rapidly from setbacks and to defy the expectations of others (“behavioral resistance”), and to initiate changes as soon as they are necessary or desirable (“behavioral dynamics”). More resilient (trainee) teachers show, among other things, lower values for anxiety as an emotional stress symptom and higher values for job engagement. The findings are discussed with regard to implications for VET teacher training and we stress the need for equilibration on a systemic perspective.